Association of laboratorial parameters and prognostic factors in uterine corpus cancer - Bezerra,Kaio Raffael Valotta (2021)
SUMMARY OBJECTIVE: The aims were to compare the red blood cells, platelet count, neutrophil-lymphocyte ratio, platelet-lymphocyte ratio, red cell distribution width, and fasting glucose in peripheral blood of patients with benign and malignant uterine neoplasms and to relate these laboratory parameters with prognostic factors and overall survival in cancer. METHODS: The results of the laboratory parameters were analyzed using the Mann-Whitney U test. Receiver operating characteristic curves were used to find the cutoff values. Overall survival was estimated using the Kaplan-Meyer method. RESULTS: Higher values of neutrophil-lymphocyte ratio and fasting glucose were found in cancer patients. Higher platelet-lymphocyte ratio values were associated with other subtypes when compared with endometrioid subtype; higher values of red cell distribution width were found in stage II/IV when compared with stage I; lower hemoglobin values were related to stage II/IV and nonendometrioid histological type. Platelet-lymphocyte ratio <145.56 was associated with longer overall survival. CONCLUSION: Hemoglobin and platelet-lymphocyte ratio values are prognostic factors in uterine corpus cancer.